2020
DOI: 10.1002/jgc4.1272
|View full text |Cite
|
Sign up to set email alerts
|

Education on cancer risk assessment and genetic counseling to address cancer health disparities among racial/ethnic groups and rural populations: Implementing culturally tailored outreach through community health educators

Abstract: While significant progress is being made in cancer prevention and treatment, opportunity exists to make a difference for populations bearing an uneven burden of the disease. Research indicates that increased inherited risk and more‐aggressive forms of cancer among underserved racial/ethnic (R/E) groups (e.g., African American/Black, American Indian/Alaska Native, Asian, Hispanic/Latino, and Native Hawaiian/Other Pacific Islander) and rural populations may explain the cancer incidence and mortality disparities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 4 publications
(4 reference statements)
0
16
0
Order By: Relevance
“…The cost of GCS was also raised by participants, an economic stability component of social determinants of health [ 24 ]. Financial barriers are a deterrent to GCS [ 25 ], and insurance status is associated with referral for genetic screening [ 1 ] and is a relevant issue of access raised in our study. Advances in genetic and genomic screening pose the risk of perpetuating cancer susceptibility screening disparities unless systemic education and access inequities are addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cost of GCS was also raised by participants, an economic stability component of social determinants of health [ 24 ]. Financial barriers are a deterrent to GCS [ 25 ], and insurance status is associated with referral for genetic screening [ 1 ] and is a relevant issue of access raised in our study. Advances in genetic and genomic screening pose the risk of perpetuating cancer susceptibility screening disparities unless systemic education and access inequities are addressed.…”
Section: Discussionmentioning
confidence: 99%
“…We recommend next steps need to further involve community partners as stakeholders in research and programming. Researchers reported successful engagement efforts, including across sectors such as academia, community-based organizations, and community clinics [5,6,8,13,16,25,26,[28][29][30]. Researchers and HCPs doing community outreach with Asian and MI subgroups need to address community beliefs and behaviors as priorities under the umbrella efforts to help people understand the difference between general and inherited cancer screening.…”
Section: Discussionmentioning
confidence: 99%
“…Study sponsors should consider clinical trial coordinators and community health educators from the same racial/ethnic groups, because they may play an impactful role in optimizing awareness and education of cancer treatment and clinical trials. This should be coupled by provision of appropriate tools in plain language that clearly explain potential benefits to patients and their families, while also highlighting race/ethnicity‐driven measures of cancer risk and outcomes 36 . Educational interventions were, in fact, shown to increase willingness to participate in clinical trials, although different tools may be needed for specific racial/ethnic minority groups 37 .…”
Section: What Can We Do About It?mentioning
confidence: 99%
“…Participation in clinical trials itself may ameliorate observed disparities in cancer outcomes, because clinical trials can provide access to evidence‐based medicines 58,59 . Achieving cancer health equity through optimizing diversity in clinical trials is a national and global imperative, and everyone has a role to play 24,36,60 …”
Section: What Can We Do About It?mentioning
confidence: 99%
See 1 more Smart Citation